Reflections on a career in operational science: some lessons learned - Jolly, Gill (Frontiers in Earth Science, 2023)
In this short essay, I reflect on my career and some of the inspirational scientists that have influenced the way I have chosen to work. I highlight some of my lessons learnt as a woman scientist in an environment that remains largely male-dominated at a senior level. Volcanology (and science more generally) as a profession has changed for the good over the last four decades, with many early and mid-career women aiming for, and achieving, senior roles. I look forward to seeing the next-generation of diverse volcanologists drive the science forward to keep communities safer from volcanic activity.